Implementation of Murabahah in Sharia Banks According to the Al-Qur'an Surah Al-Baqarah Verse 275 - Zamroni, M Afif; Purwati, Lisa; Kausar, Shakila (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
Murabahah is an effort to find sustenance through buying and selling. Murabaha is buying and selling based on consensual between the two parties who transact. This article aims to find out the implementation of Murabahah in Islamic banking according to the Qur'an Surah al-Baqarah verse 275. Why Murabaha financing dominates compared to other financing. This writing method uses a book survey technique (library research) regarding the literature related to the implementation of murabahah. The result of this article is that Murabahah is permissible and does not conflict with the teachings of Islamic Shari'ah. Murabahah financing is widely used because it has a relatively lower risk, both from the bank and the customer side. From the customer's side, there is certainty about the number of installments because, in this buying and selling scheme, the margin value (bank profit) is set which does not change until the financing is paid off.